2021
DOI: 10.1039/d1tb01237a
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning enabled classification of real-time respiration signals acquired by MoSSe quantum dot-based flexible sensors

Abstract: : Respiration rate is a vital parameter which is useful for earlier identification of diseases. In this context, various types of devices have been fabricated and developed to monitor different...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…To improve the comprehensive performance of the sensor, researchers have carried out a lot of research on conductive materials, flexible substrates, and sensor structures. Among them, conductive materials mainly include zero-dimensional materials , (precious metal particles, polymer particles, etc. ), one-dimensional materials , (carbon nanotubes, metal wires, nanofibers, etc.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the comprehensive performance of the sensor, researchers have carried out a lot of research on conductive materials, flexible substrates, and sensor structures. Among them, conductive materials mainly include zero-dimensional materials , (precious metal particles, polymer particles, etc. ), one-dimensional materials , (carbon nanotubes, metal wires, nanofibers, etc.…”
Section: Introductionmentioning
confidence: 99%
“… 42 Recently, Bokka et al fabricated a water-soluble MoSSe quantum dots/poly(vinyl alcohol) (PVA) film as a humidity sensor that was capable of discerning different breathing patterns. 43 The breathing data were analyzed using a neural network algorithm for classifying them into different breathing patterns. Liu et al recently fabricated a fabric-based humidity sensor using a hydrophobic-hydrophilic patterned polyester-spandex fabric as a substrate that was subsequently treated with polydopamine-acid carbon nanotubes (aCNTs) that were quick and sensitive to a large humidity range.…”
Section: Introductionmentioning
confidence: 99%
“…In this aspect, Rauf et al reported a smart textile containing a MOF film grown using the Langmuir–Blodgett (LB) technique resulting in a sensor capable of detecting water vapor in the presence of several volatile organic compounds . Recently, Bokka et al fabricated a water-soluble MoSSe quantum dots/poly­(vinyl alcohol) (PVA) film as a humidity sensor that was capable of discerning different breathing patterns . The breathing data were analyzed using a neural network algorithm for classifying them into different breathing patterns.…”
Section: Introductionmentioning
confidence: 99%
“…40 With the development and popularity of smart wearable devices, machine learning has received growing interest in the area of health and motion monitoring. 41 In particular, the convolutional neural networks (CNNs)-assisted deep learning approach, which is structured as a series of convolutional layers and pooling operation, shows promise for improving the accuracy and reliability of processing complex signals such as physiological signals and complex human activities. 42 In this work, a fully integrated patch for wireless intelligent respiratory monitoring is proposed, and its schematic layout is shown in Figure 1a.…”
mentioning
confidence: 99%